ATS Route Design Between PKY VOR Palangka Raya and PNK VOR Pontianak - Wahid Zulfikar, Muhammad Nabil; Putriekapuja, Rany Adiliawijaya; T.U, Wisnu Darjono (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
Air Traffic Controllers have two main objectives, namely ensuring flight safety and creating maximum efficiency for the orderly flow of air traffic. This study aims to find out and solve problems that occur related to IFR flights from Palangka Raya to Pontianak because there is no ATS Route. This study uses the Research and Development level one method with data collection techniques, namely preliminary studies using gap analysis, needs analysis using interviews, and validation using interviews with experts in the field of Aviation.